(3NdGUI GdYLGdI aj HjGf eQGO GdQSGdIs - (3MSf Hf ESeGYjd Hf YHO Gddg GdOQcRdi GdehUdjs; (3MSf Hf ESeGYjd Hf YHO Gddg GdOQcRdj GdehUdjs
(3ChdgG (B:s
(3Cfi deG QCjJ HYV GdEWGdI ai GdYLGdI eNJUQ TQMi GdebGdI GdhGbY Ydi GdQSGdI GdeQJHI s
(3BNQgG (B:s
(3HeG CQOfGg ef GdTQM GdTQja GdPi gh ef JbQjQ GdYRjR GdYdje hCf jMaXg ceG MaX CUhdg ef GdJMQja hGdEfJbGO Je GdcJGH HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs